(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2023)
Our paper is situated within the broader exploration of the epistemic and aesthetic potential of biomedical imaging technologies on the human lived experience. Intra-Active Sense-Making is guided by the grounding thesis that imaging technology ought to be understood as a set of material, rhetorical and performative processes, and as a way to challenge the ocularcentric presuppositions. By drawing on the new materialistic theses that phenomena are not pre-existent to intra-action, and that agency should be understood as distributed on human, animal, objectual, and ‘physical’ levels, we offer a performative understanding of biomedical imaging operations complementary to the reflective paradigm. Biomedical imaging may be understood through our idea of intra-active sense-making; while much literature states that medical imaging establishes a view of the self as quantified, atomized, and governable, we argue that the co-configuration of human senses and digital sensors is a source of new sense-making capabilities.